Benefits to University Students Through Volunteering in a Health Context: A New Model. Issue 3 (3rd July 2018) - Williamson, Iain; Wildbur, Diane; Bell, Katie; Tanner, Judith; Matthews, Hannah
ABSTRACT: Individual interviews explored 50 British University students' accounts of sustained volunteering within health settings and a model was developed using grounded theory. Phase one – 'Getting involved' – outlines 'motives and catalysts' for students starting to volunteer wherein altruistic motives of compassion for others are juxtaposed with perceptions of enhanced employability. Phase two – 'Maintaining commitment' – includes three components ('Making connections', 'Developing resilience' and 'Keeping the balance'), which represent important aspects of continuing volunteering participation. Phase three – 'Reaping the rewards' – focuses on the benefits of volunteering including self-development. Our findings have implications for the training and support of student volunteers.